THE IMPACT OF CLIMATE CHANGE ON EDUCATION - Yaqubova Sarvinoz Zafarbek qizi; Yaqubjonova Ro‘zixon Mirkomil qizi (TADQIQOTLAR, 2025)
Annotation: This thesis examines the key problems faced in online education and provides possible solutions to overcome them. In particular, factors such as limited access to technical means and the Internet, lack of live communication between students and teachers, difficulties in self-motivation, as well as concentration and effective time management are considered. The study has important theoretical and practical significance for educational systems that are transitioning to online learning.